Russian and Foreign Experience of AntiCrisis Planning of 2008-2010 and Efficiency Estimation of Conducted AntiCrisis Programs - A. R. Shakirov; O. Yu. Sinyaeva (Управление)
Another crisis requires mobilization of all knowledge, including experience of the mistakes. The crisis of 2008 is the actual guidance for minimizing crisis consequences. Of course, the reasons for the current and the previous crisis are fundamentally different, and are mostly regional rather than global, by nature. But the consequences for both are the same – fall of living standards, the collapse of the banking system, reduction of economic diversification. That is why it becomes so important for government to make both a rational and effective anti-crisis plan. The global financial crisis of 2008, which is under our consideration, originated in the United States as a result of the mortgage crisis. The phenomenon was spreading rapidly in the rest of the world. In particular, Russia immediately took a number of measures to reduce the negative effects in the first months. Subsequently, all the activities have merged into a single set of measures called “Anti-crisis program of the Russian Federation” (2009) and “The main directions of anti-crisis measures of the Russian Federation for 2010”. Programs had both positive and negative effects on the economic recovery. However, in total, they have helped Russia to overcome the crisis stage without catastrophic losses, which was even noted by the World Bank. The experience of some foreign countries is also subject to review because of their effectiveness and difference from the Russian one. It also complements the picture of the anti-crisis measures and makes it more solid and global. Tracing the history of the 2008 crisis, we can conclude that the state, fighting the crisis phenomena, was concerned with statistical indicators only, without regard for the lives of their citizens. In this scenario, the developed countries must learn to overcome the crisis with minimal state intervention, but a strong motivating effect.